Implementasi Peraturan Walikota Salatiga Nomor 118 Tahun 2020 Perspektif Siyasah Syari’yyah (Studi Penyelenggaraan Ketertiban Umum Di Kelurahan Mangunsari Kota Salatiga) - Iroh markamah; Cholida Hanum (Constitutional Law and Siyasah Department, Sharia and Law Faculty, IAIN, 2024)
According to Article 14 Paragraph 2 Letter D of Salatiga Mayor Regulation No. 118/2020, the lurah has the duty to ensure security and public order in the community at the kelurahan level. This is also in line with the concept of Imamah in Siyasah Shari'yyah, where a leader must provide security for the benefit of his people. However, in Salatiga itself, there are still violations of public order. Therefore, this study is designed to find out how the implementation of Salatiga Mayor Regulation No. 118/2020 in the implementation of security and public order in Mangunsari Urban Village in Salatiga City and the benchmarks for the implementation of security and public order in Mangunsari Urban Village in Salatiga City based on the concept of Siyasah Shari'yyah. The type of research used is empirical legal research. The results of the study found that the implementation of Salatiga Mayor Regulation No. 118/2020 in organizing public security and order in Mangunsari Urban Village is not maximally implemented, due to the lack of awareness of the community in carrying out night watches at the Ronda Post, which is the result of not coordinating a number of residents by the urban village considering the large number of residents. Furthermore, the benchmarks for the implementation of public security and order in Mangunsari Urban Village in Salatiga City, based on the concept of Siyasah Shari'yyah, have also not been achieved, as there are many violations of public security and order. This is not in accordance with the concept of Siyasah Shari'yyah, namely the principles of Wahdatul Ummah, Al-Adalah, Karomah Insaniyah, Al-Musawah, Tasamuh, human cooperation, Al-Huriyah, Al-Huriyah, and Al-Ahklak Al-Karimah. As well as Ad-dharu yuzalu (harm must be eliminated; Jalbul mashalih wa daf'ul mafasid (achieving benefit and rejecting harm); al-mashlahul 'ammah muqaddamah 'alal mashlahatil khasshah (public benefit takes precedence over private benefit).